2004
DOI: 10.1007/s00425-003-1121-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a protein of the plastid inner envelope having homology to animal inorganic phosphate, chloride and organic-anion transporters

Abstract: A protein from Arabidopsis thaliana (L.) Heynh. showing homology to animal proteins of the NaPi-1 family, involved in the transport of inorganic phosphate, chloride, glutamate and sialic acid, has been characterized. This protein, named ANTR2 (for anion transporters) was shown by chloroplast subfractionation to be localized to the plastid inner envelope in both A. thaliana and Spinacia oleracea (L.). Immunolocalization revealed that ANTR2 was expressed in the leaf mesophyll cells as well as in the developing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 52 publications
1
47
2
Order By: Relevance
“…Like TPT, both of these Pi transporters are located in the chloroplast inner envelope membrane. 14,18 Also, transcript levels for the genes increased when plants were exposed to light, although the delay in PHT4;4 transcript accumulation may reflect regulation by photosynthates rather than a direct response to light. It is formally possible that PHT4;4 and PHT2;1 also maintain stromal Pi concentrations through export.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like TPT, both of these Pi transporters are located in the chloroplast inner envelope membrane. 14,18 Also, transcript levels for the genes increased when plants were exposed to light, although the delay in PHT4;4 transcript accumulation may reflect regulation by photosynthates rather than a direct response to light. It is formally possible that PHT4;4 and PHT2;1 also maintain stromal Pi concentrations through export.…”
Section: Methodsmentioning
confidence: 99%
“…16 Proteomic analysis of the chloroplast envelope and envelope membrane fractionation studies confirmed that PHT4;4 is located in the chloroplast inner envelope membrane. 4,17,18 In contrast, PHT4;1 is located in the thylakoid membrane. 4 Despite the localization of these two proteins to chloroplast membranes, transcripts for all of the Arabidopsis PHT4 genes have been detected in roots as well as leaves suggesting that the encoded plastid-targeted proteins also function in non-photosynthetic plastids.…”
Section: Research Papermentioning
confidence: 97%
See 1 more Smart Citation
“…We found two candidates that differed in transcript abundance for P i transporters (PHT4.4 and PHO1-H8) and one misexpressed K + efflux transporter (KEA1) (see Supplemental Tables 4 and 5 online). All three transcripts were more highly expressed in the mesophyll; however, PHT4.4 has previously been localized to the chloroplast (Roth et al, 2004), and PHO1-H8 and KEA1 are predicted to be targeted to the mitochondria and chloroplast, respectively (SUBA database) (Heazlewood et al, 2007). Further support for the role of KEA1 in chloroplasts comes from its closest two homologs in barley also being highly expressed in the mesophyll (Richardson et al, 2007).…”
Section: Cell-specific Ca Compartmentation Involves Cell-specific Sementioning
confidence: 99%
“…The theoretical molecular mass of the processed protein is 50.5 kD, which differs significantly from the 35 kD estimated from SDS-PAGE. Two other members of the PHT4 family, PHT4;1 and PHT4;4, also exhibit anomalous migration by SDS-PAGE (Roth et al, 2004;Ruiz Pavó n et al, 2008). The faster gel migrations of PHT4;2 and these other PHT4 proteins may be a function of overproportional binding of SDS, which is common for highly hydrophobic integral membrane proteins (Rath et al, 2009).…”
Section: Localization Of Pht4;2 To Root Plastidsmentioning
confidence: 99%